Recurrence of Anti-N-Methyl-D-Aspartate Receptor Encephalitis: A Cohort Study in Central China - Feng, Jilun; Yang, Mu; Cui, Dingge; Huang, Zhi; Ji, Tuo; Lian, Yajun (Frontiers in Neurology, 2022)
Abstract Objective To investigate factors that could impact or predict the probability of anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis recurrence in central China. Methods From November 2014 to October 2020, observational data of anti-NMDAR encephalitis inpatients in our institution were collected and analyzed prospectively. The demographics, clinical characteristics, tumor status, lesion locations on MRI and immunotherapies, etc. had entered into a Cox regression model for the identification of the factors associated with relapse-free survival. Results We enrolled 113 patients in a row (median age: 28 years, range: 1-61 years). The gender distribution was not statistically significant (p=0.158), with 49 people (43.4 percent) being female. The median follow-up time was 16 (4-77) months. Among them, 16.8% of patients relapsed. The average interval between recurrences was 8 months (range 3-54mo). The severity of the initial relapse was less severe than it had been at the start. The first relapse had considerably fewer symptoms (median 2, range 1-6) than the first episode (median 4, range 1-8, p=0.005). The mRS at first relapse (median 3, mean 2.84, range 1-5) had been significantly lower than that at onset (median 4, mean 3.89, range 3-5, p=0.004). The length of hospitalization at first relapse (median 35 days, range 14-102) was significantly shorter than the first episode (median 17 days, range 5-46, p=0.002). In the survival analysis, the risk of recurrence was significantly higher for patients with a brainstem lesion (HR: 4.112, 95%CI: 1.205-14.030; p=0.024) or ≥3 abnormal sites (HR:2.926,95%CI: 1.085-7.896; p=0.034) on brain MRI at the first episode. There was no significant difference in neurological outcomes between the recurrent and monophasic groups at the most recent follow-up (mRS 0–2 in 17/19 vs 86/94; p = 0.674). Conclusions Anti-NMDAR encephalitis can recur in around one out of every six cases, and symptoms are generally milder than when it first appears. Recurrence is not related to the severity in the acute phase or the prognosis at follow-up. Patients with ≥ 3 abnormal sites on MRI or lesions located in the brainstem at onset must be alert to the possibility of recurrence.